Presence and Impact of Uterine Fibroids in Women with Menstrual and Premenstrual Syndrome – A Statistical Analysis - Anuradha , R.; Rathi , G. (International Journal of Membrane Science and Technology, 2023)
A number of non-invasive alternatives to hysterectomy are available for treating uterine fibroids, but they may not effectively relieve all symptoms. As a result, it has become increasingly important to use patient-reported outcomes to assess the success of these alternative therapies in reducing uterine fibroid symptoms. These symptoms can range from heavy menstrual bleeding to dysmenorrhea for women who experience menstrual and premenstrual syndrome. To standardize the assessment of fibroid-related symptoms, the Uterine Fibroid Indicators and Analysis of Patient Recovery survey form (UFS-APR) was developed as a patient-recovery report analysis. The UFS APR is used to analyze womenfolk with uterine fibroids existing with menstrual and premenstrual syndrome. In our study, we had translated and validated the UFS-APR in India to examine its reliability, correctness, scope, validity and responsiveness in assessing the treatment of uterine fibroids.